Paralemnolins V and W, New Nardosinane-Type Sesquiterpenoids from a Bornean Soft Coral, Lemnalia sp. - Chin, Soon Phan; Takashi Kamada; Kishio Hatai; Charles Santhanaraju Vairappan (2018)
Two new nardosinane-type sesquiterpenoids, paralemnolin V (1) and paralemnolin W (2), along with five known sesquiterpenoids (3–7), were isolated from a population of Bornean soft coral Lemnalia sp. The structures of these metabolites were elucidated based on their NMR and HR-ESI-MS spectral data. These compounds were subjected to antibacterial and antifungal tests against eight bacterial and seven fungal strains.